Circulação, desenvolvimento econômico e ordenamento territorial: elementos teóricos para análises de pesquisas sobre a Rota de Integração Latino Americana - Ana Paula Camilo Pereira; Mateus Boldrine Abrita; Rafael Oliveira Fonseca (Confins)
The Latin American Integration Route (Rila) is an international transport corridor under implementation with the purpose of connecting Brazil, Paraguay and Argentina to the ports in northern Chile. It is an infrastructural project that has generated recurring socioeconomic and scientific debates, especially in Mato Grosso do Sul, whether due to its repercussions on material and immaterial circulation, on economic development and, consequently, on spatial planning, with direct positive and negative impacts on its path. Therefore, this research aims to carry out an analysis of the theoretical elements on circulation, economic development and spatial planning in order to offer theoretical and conceptual support for the resulting research in the scope of Rila. For this purpose, a discussion of circulation is presented in the article, after we present an analysis of the possibilities of economic development, then we will approach the issue of spatial planning and, finally, some final considerations.